(untitled) (Південний архів (історичні науки), 2024)
The article focuses on the civil resistance of the residents of Kherson and Kherson region in March – early April 2022 during the Russian full-scale invasion of Ukraine. Objective. The study focuses on peaceful demonstrations against the Russian occupation that took place in Kherson, Kakhovka, Nova Kakhovka, Gola Prystan, Genichesk, Skadovsk and other settlements of the region. The author analyzes the preconditions for peaceful actions as part of the civil resistance of the population, their course and significance. The article establishes the chronology of the main demonstrations against the occupiers that took place in Kherson and the region. Research methods. The source base is analyzed, consisting of operational information disseminated by the General Staff of the Armed Forces of Ukraine in open sources, information from the Institute for the Study of War (ISW), the media and eyewitness accounts of participants in the events. Results of the study: the main prerequisites for the emergence of civil resistance in Kherson and the region, the motivation of the resistance participants, the forms and chronology of resistance, the types of opposition to the Russian occupation authorities to the demonstrations, the reasons for the termination of the demonstrations as a form of resistance and their significance. Conclusions. The full-scale Russian invasion of February 24, 2022, was accompanied by mass casualties among the population of Kherson and the region, caused the destruction of civilian infrastructure and housing, and was aimed at seizing Ukrainian territories and deploying a bridgehead for a further offensive against Ukraine. This provoked mass protests by the civilian population in March 2022, which spread throughout the region and lasted until early April 2022. Peaceful protests military aggression did not stop the occupiers’ provocations, intimidation of protesters with weapons, arrests, and torture. The increase in the number of Russian troops in Kherson and the region turned the resistance from a public to a non-public format, which was intended to support the actions of the Armed Forces at the front. The civil resistance in Kherson and the region played an important role: it inspired Ukrainians to further resist the occupiers, and became part of the Ukrainian people’s resistance to Russian aggression, similar to the Resistance Movement during World War II, which fought against Nazism.